2020
DOI: 10.3389/fcell.2020.00458
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stromal Cell (MSC) Characteristics Vary Among Laboratories When Manufactured From the Same Source Material: A Report by the Cellular Therapy Team of the Biomedical Excellence for Safer Transfusion (BEST) Collaborative

Abstract: Background: Culture-derived mesenchymal stromal cells (MSCs) exhibit variable characteristics when manufactured using different methods and different source materials. The purpose of this study was to assess the impact on MSC characteristics when different laboratories propagated MSCs from cultures initiated with BM aliquots derived from the same donor source material. Methods and Methods: Five aliquots from each of three different BM donors were distributed to five independent laboratories. Three laboratories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…A striking example illustrating the influence of different isolation, culture, and cryopreservation methods was demonstrated by Stroncek et al in an experiment in which MSCs were manufactured from the same source material [ 33 ]. The authors pointed out that “manufacturing of MSCs by five independent centers contributed more to MSC variability than did the source material of the bone marrow” used in the study.…”
Section: Introductionmentioning
confidence: 99%
“…A striking example illustrating the influence of different isolation, culture, and cryopreservation methods was demonstrated by Stroncek et al in an experiment in which MSCs were manufactured from the same source material [ 33 ]. The authors pointed out that “manufacturing of MSCs by five independent centers contributed more to MSC variability than did the source material of the bone marrow” used in the study.…”
Section: Introductionmentioning
confidence: 99%
“…The presented characterization concept could have missed relevant, currently unknown, distinctive functional MSC features. To conclusively assess possible therapeutic differences, in vivo studies in adequate preclinical models are suggested, ideally in a multicenter study setting, as a recent study showed that the local manufacture process highly affects functional and molecular differences between MSC preparations ( Stroncek et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Stroncek et al described functional and molecular differences between the MSC of three patients produced in five different laboratories, despite the fact that the origin of these cells was the same [ 327 ]. These situations occur because, today, there is no standardized protocol for each one of four key steps of the MSC manufacturing process: donor MSC selection and collection, maintenance and transport of the MSC from the collection site to the processing site, culture strategy (i.e., plating cells, passaging the adherent cells, and harvesting the MSC), and cryopreservation and storage of the manufactured MSC.…”
Section: Need Of New Strategies Of Msc Productionmentioning
confidence: 99%